Know dyslexia, overcome Dyslexia: a strategic public communication campaign to raise Dyslexia Awareness in Singapore: in collaboration with the Dyslexia Association of Singapore (DAS) - Tor, Pamela Das (2008)
This document employs a variety of measures, which form the components of a strategic public communicatino campaign.